Gambaran peri-implantitis pada CBCT (Cone-Beam Computed Tomography) - Indra Gunawan; Farina Pramanik (Ikatan Radiologi Kedokteran Gigi Indonesia, 2020)
Objectives: This paper is aimed to report a case of peri-implantitis which is diagnosed using CBCT. Case Report: A 61 year old male was referred to a dental radiology unit for CBCT examination. The patient complained of pain in the area of ​​the tooth where the implant was attached. CBCT results show there is inflammation around the implant that has been inserted, characterized by a visible radiolucent area in 1/3 of the cervical implant on the mesial, distal, buccal / labial and palatal sides with varying sizes on each side. Based on the radiograph findings, the diagnosis of peri-implantitis was confirmed. Conclusion: Peri-implantitis is inflammation around the implant which results in a condition in the form of bone loss around the implant that is placed. Radiographic examination such as CBCT can be an excellent choice to help diagnose peri-implantitis by seeing a clearer 3-dimensional radiograph.